Deletion genotypes reduce occlusion body potency but increase occlusion body production in a Colombian Spodoptera frugiperda nucleopolyhedrovirus population - Barrera, Gloria; Trevor, Williams; Villamizar, Laura; Caballero, Primitivo; Oihane, Simón (Public Library of Science, 2024)
The Colombian field isolate (SfCOL-wt) of Spodoptera frugiperda nucleopolyhedrovirus (SfMNPV) is a mixture of different genotypes. To evaluate the insecticidal properties of the different variants in SfCOL-wt a plaque assay was performed and ten distinct genotypes were identified (called A through J). SfCOL-A was the most prevalent (71±9%) and showed a PstI restriction profile identical to that of SfCOL-wt. The remaining nine genotypes presented genomic deletions of 3.8-21.8 Kb, located between nucleotides 11.436 and 33.883 in the Nicaraguan genotype of SfMNPV (SfMNPV-B). These deletions affected the region between open reading frames (ORFs) sf20 and sf33. The potency of SfCOL-A occlusion bodies (OBs) was 4.4-fold higher than SfCOL-wt OBs, whereas the speed of kill of SfCOL-A was similar to that of SfCOL-wt. Deletion genotype OBs were similarly or less potent than SfCOL-wt but six deletion genotypes were faster killing than SfCOL-wt. The potency of mixtures of OBs and co-occluded mixed genotype OBs were consistently reduced in twogenotype mixtures involving equal proportions of SfCOL-A and one of three deletion genotypes (SfCOL-C, -D or –F). Speed of kill and OB production were improved only when the certain genotype mixtures were co-occluded, although OB production was higher in the SfCOL-wt isolate than in any of the component genotypes or mixtures thereof. We conclude that the SfCOL-wt population is structured to maximize the production of OBs in each infected host.